До типології та інтерпретації антропоморфних надгробків Херсонеса Таврійського - Буйських, A.B.; Зубар, В.М. (Археологія, 2006)
У статті запропоновано нову типологію антропоморфних надгробків некрополя Херсонеса Таврійського античної доби, зроблено спробу з’ясувати місце та семантичне значення цих пам’яток у поховальній практиці херсонеситів. Статья посвящена разработке новой типологии антропоморфных памятников некрополя Херсонеса Таврического. В основу классификации положен формообразующий признак, в результате чего выделены два основных типа надгробий—объемные скульптурные и рельефные, внутри которых выделено несколько вариантов. Для первого типа они определены прорисовкой основных деталей — головы, плеч, тулова фигур, для второго — характером прорисовки изображения, выполненного в низком рельефе или врезными линиями. Исходя из условий находок, предложена семантическая трактовка надгробий как апотропеев — одной из составляющих консервативного характера погребального культа херсонеситов на протяжении всей античной эпохи. Прослежена связь памятников с идеей героизации умерших. The article is devoted to the development of new typology of anthropomorphic monuments from the necropolis of Tauric Chersonesos. Following that the classification is based on the form-making feature the two main types of gravestones are singled out. They are sculptures and relief images with variants distinguished within them. In the first type they are determined by the outline of the main details such as head, shoulders, body of the figures; for the second type they are based on the nature of outline of the image implemented in low relief or with carved lines. Reasoning from the discovery conditions the authors suggested semantic interpretation of gravestones as apotropei, one of the components of the conservative nature of burial cult of Chersonesites during whole the Ancient epoch. They also traced the connection of the monuments with the idea of heroization of the dead.